Toll-Like Receptor 4 Triggering Promotes Cytosolic Routing of DC-SIGN-Targeted Antigens for Presentation on MHC Class I - Horrevorts, Sophie K.; Duinkerken, Sanne; Bloem, Karien; Secades, Pablo; Kalay, Hakan; Musters, René J.; van Vliet, Sandra J.; García-Vallejo, Juan J.; van Kooyk, Yvette (Frontiers in Immunology, 2018)
DC-SIGN is an antigen uptake receptor expressed on dendritic cells (DCs) with specificity for glycans present on a broad variety of pathogens and is capable of directing its cargo to MHC-I and MHC-II pathways for the induction of CD8+ and CD4+ T cell responses, respectively. Therefore, DC-SIGN is a very promising target for the delivery of antigen for anti-cancer vaccination. Although the endocytic route leading to MHC-II presentation is characterized to a large extent, the mechanisms controlling DC-SIGN targeted cross-presentation of exogenous peptides on MHC-I, is are not completely resolved yet. In this paper, we used imaging flow cytometry and antigen specific CD8+ T cells to investigate the intracellular fate of DC-SIGN and its cargo in human dendritic cells.Using different techniques w e investigated the intracellular fate of DC-SIGN and its cargo during cross-presentation in DCs. Our data demonstrates that both immature DCs and Toll-like receptor (TLR4) 4 stimulated DCs (TLR4)-stimulated DCs are had similar internalization capacity and were both able to cross-present antigen targeted via DC-SIGN. Interestingly, while the internalization capacity of DC-SIGN was similar in immature and TLR4-stimulated DCs, simultaneous triggering of TLR4 and DC-SIGN in DCs resulted in the translocation of cargo to the cytosol, leading to proteasome-dependent processing and increased CD8+ T cell activation. Understanding the dynamics of DC-SIGN-mediated uptake and processing is essential for the design of optimal DC-SIGN-targeting vaccination strategies aimed at enhancing CD8+ T cell responses.